2021
DOI: 10.3390/ijerph18041991
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety-Free Life Expectancy by Sex and Urban–Rural Areas in Jiangxi, China in 2013 and 2018

Abstract: To quantitatively estimate life expectancy (LE) and depression and anxiety-free life expectancy (DAFLE) for the years 2013 and 2018 in Jiangxi Province, China, by sex and urban–rural areas. Additionally, to compare the discrepancy of DAFLE/LE of different sexes and urban-rural areas over various years. Methods: Based on the summary of the health statistics of Jiangxi Province in 2013 and 2018 and the results of the 5th and 6th National Health Service Surveys in Jiangxi Province, the model life table is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Although women have a longer life expectancy, the prevalence of depression is also higher among them (Salk et al, 2017 ). Consistently, previous research has shown a differential impact of depression on healthy life expectancies, depending on gender, with women at all ages expecting to live a higher proportion of their life with depression (Andrade et al, 2016 ; Alves and Pereira, 2018 ; García et al, 2019 ; Wu et al, 2021 ; Bramajo, 2022 ).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although women have a longer life expectancy, the prevalence of depression is also higher among them (Salk et al, 2017 ). Consistently, previous research has shown a differential impact of depression on healthy life expectancies, depending on gender, with women at all ages expecting to live a higher proportion of their life with depression (Andrade et al, 2016 ; Alves and Pereira, 2018 ; García et al, 2019 ; Wu et al, 2021 ; Bramajo, 2022 ).…”
Section: Introductionsupporting
confidence: 71%
“…The CIDI-SF cannot rule out that the symptoms are due to other mental health problems or grief. However, previous studies about life expectancy free of depressive symptoms have used screening tools for depression (Drummond Andrade et al, 2016 ) or self-reported diagnosis (Alves and Pereira, 2018 ; Wu et al, 2021 ). When interpreting the results of our study, it is important to take into account that the prevalence of depressive symptoms overestimates the prevalence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the following variables because of their identified influence on depression in China, including residence place (urban vs rural), self-rated health status (poor or lower, fair, and good or above), and survey year (2016 or 2018) [ 13 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…We investigated socio-demographic characteristics including age (years), gender (male vs. female), marital status (married/cohabitation, never married, and widowed/divorced/separated), education attained (illiterate, primary school, middle school, high school or equivalent, and bachelor or above), minority ethnicity (yes or no), and average annual household income per person. We also investigated the following variables because of their identified influence on depression in China, including residence place (urban vs. rural), and self-rated health status (poor or lower, fair, and good or above) ( 10 , 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…In China, about 15.9-38.6% of the general population suffer from common mental health problems (2,(4)(5)(6)(7), and females are nearly twice as likely to have common mental health problems as males (5,6). Previous studies have also estimated the prevalence of mental disorders by age, gender, and year (2,(8)(9)(10)(11). To improve the worrying mental health situation, it has significant practical implications for policymakers in China to understand the temporal trend of prevalence and treatment of mental disorders.…”
Section: Introductionmentioning
confidence: 99%